2016
DOI: 10.2174/1574892810666151102110248
|View full text |Cite
|
Sign up to set email alerts
|

Saffron-Based Crocin Prevents Early Lesions of Liver Cancer: In vivo, In vitro and Network Analyses

Abstract: Taken together, our findings introduce crocin as a candidate chemopreventive agent against HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…Administration of GSE to DEN-2AAF-treated rats in this work counteracted DEN-2AAF-induced oxidative stress as shown by the restoration of antioxidant levels of SOD and CAT in the liver and the diminishing of important markers of oxidative stress, such as MDA and P.Carbonyl. DEN-2AAF-induced CAT activity has been similarly shown to be increased in cancer cells, most likely, to favor cell proliferation by inducing genetic instability and activation of oncogenes 6 , 34 . The prevention of oxidative stress by GSE might be attributed to its potent antioxidant capacity that was confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of GSE to DEN-2AAF-treated rats in this work counteracted DEN-2AAF-induced oxidative stress as shown by the restoration of antioxidant levels of SOD and CAT in the liver and the diminishing of important markers of oxidative stress, such as MDA and P.Carbonyl. DEN-2AAF-induced CAT activity has been similarly shown to be increased in cancer cells, most likely, to favor cell proliferation by inducing genetic instability and activation of oncogenes 6 , 34 . The prevention of oxidative stress by GSE might be attributed to its potent antioxidant capacity that was confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] There are already studies showing the therapeutic value of crocin as anticonvulsant, antiinflammatory, antidepressant and antitumor molecule. [9][10][11][12][13] There are already studies showing the therapeutic value of crocin as anticonvulsant, antiinflammatory, antidepressant and antitumor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that crocin exhibits protective roles in liver diseases. Crocin not only prevents early liver damages of liver cancer 21 , 22 but it also directly suppresses cell survival in HCC by targeting different downstream effectors to inhibit proliferation and induce apoptosis. 13 Considering the important roles of autophagy in cell homeostasis, here, we explored its roles in crocin-associated apoptosis.…”
Section: Introductionmentioning
confidence: 99%